The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/risks5010016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Extensions to Coherent Mortality Forecasting Models

Abstract: Coherent models were developed recently to forecast the mortality of two or more sub-populations simultaneously and to ensure long-term non-divergent mortality forecasts of sub-populations. This paper evaluates the forecast accuracy of two recently-published coherent mortality models, the Poisson common factor and the product-ratio functional models. These models are compared to each other and the corresponding independent models, as well as the original Lee-Carter model. All models are applied to age-gender-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Study done by Shamshimah and Noriszura [12] shows that the Malaysian population especially the working men are more likely to become disabled or die than women employees hence reverse mortgages is an alternative for them to prepare for their after retirement in the future. While Syazreen, Purcal and Parr [15] found that based on coherent among Malays, Chinese and Indians in Malaysia, Chinese has lower mortality rates.…”
Section: Introductionmentioning
confidence: 96%
“…Study done by Shamshimah and Noriszura [12] shows that the Malaysian population especially the working men are more likely to become disabled or die than women employees hence reverse mortgages is an alternative for them to prepare for their after retirement in the future. While Syazreen, Purcal and Parr [15] found that based on coherent among Malays, Chinese and Indians in Malaysia, Chinese has lower mortality rates.…”
Section: Introductionmentioning
confidence: 96%
“…A number of studies have compared the empirical characteristics and/or accuracy of selected recently developed mortality models (e.g. Booth et al 2006 , Cairns et al 2009 , Scherbov and Ediev 2016 , Shair et al 2017 , Stoeldraijer et al 2013 , and Terblanche 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the young adult age (15-25), the male mortality rates show non-linear pattern compared to the female mortality rates. According to Shair et al (2017aShair et al ( , 2017b, this significant difference might be coming from the 73% of road accidents involving male teenagers. In addition, the plot portrays the data suggesting that women tend to live longer than man.…”
Section: Data Descriptionmentioning
confidence: 99%
“…A great deal of research has been conducted on the study of multi-population mortality models outside Malaysia, yet only a small number of research has been conducted on the study of coherent mortality model in Malaysia. Shair et al (2017aShair et al ( , 2017b are the only authors that have compared coherent mortality model with its independent model in Malaysia. They found that the multi-population mortality model outperformed the single-population mortality model in terms of overall forecast accuracy.…”
Section: Introductionmentioning
confidence: 99%